Abraham and Nimrod in the Shadow of Zarathustra - Kiel, Yishai (The journal of religion, 2015)
The article focuses on a rabbinic story which tells the casting of Abraham into a fiery furnace by Nimrod and provides insights that reimagines and reconfigures the Nietzschean figure of Zarathustra in Late Antiquity. Topics covered include how the authors of the rabbinic narrative used a diverse array of Greek sources related to the figure of Zarathustra and how the intersections of the early biographies of Abraham and Zarathustra sparked the imagination of pre-Islamic authors.